Subclavian Reconstruction In Superior Sulcus Tumor: Case Report - Demirkaya, Ahmet; ERŞEN, Ezel; KAYNAK, Mehmet Kamil; AKÇIL, Murat; ALTAN, Seyfettin Hakan; AKGÜN, Özerk Özgür (Cerrahpaşa Medical Journal, 2014)
Superior sulcus tumors are primary lung tumors with a characteristic clinical presentation of pain in the eighth cervical, first and second thoracic trunk distribution and Horner syndrome caused by stellate ganglion invasion. Superior sulcus tumors has a privilidged position in lung cancers because of its proximity to brachial plexus, subclavian vessels and vertebral body. Although subclavian artery involvement is known to be a negative prognostic factor, patients who underwent a procedure with subclavian artery resection showed better survival compared with the ones without arterial resection. A male patient aged 48, had undergone simultaneous mediastinoscopy and left posterolateral thoractomy with upper lobectomy + 1st.-2nd. costae resection + subclavian artery resection + PTFE graft interposition. After radiotherapy, during follow-up, graft trombosis was discovered with the symptoms of left arm claudication. Left carotico-subclavian PTFE graft bypass was performed. No complication and recurrence developed in the 12th month follow-up .